Silver foil dry granular glaze, ceramic tile with silver foil decorative effect and preparation method of ceramic tile
By developing silver foil dry-grain glaze and optimizing its formulation and firing process, the problem of high-temperature deformation and durable gloss on building ceramics is solved, and better silver foil gloss effect and stability are achieved.
Patent Information
- Application Number
- CN202411762691.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The application of silver foil in architectural ceramics has problems such as high temperature deformation, lack of gloss and color, making it difficult to maintain the design pattern and shape.
A silver foil dry-grain glaze, including silver foil core and silver foil base slurry, was developed to improve the sintering temperature and bondability of silver foil cores by optimizing the formulation and firing process.
The stability and gloss effect of silver foil in high-temperature firing of ceramics are achieved, and the problems of silver foil not lasting, poor gloss and poor stability are solved.
Smart Images

Figure CN119569338A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic production technology, and in particular relates to a silver foil dry granular glaze, a ceramic tile with a silver foil decorative effect and a preparation method thereof. Background Art
[0002] Silver foil is often used to make crafts and decorations because of its high gloss and sense of nobility. In the field of ceramics, silver foil is mainly used for the post-processing of artistic ceramic products, and is decorated by silver pasting or silver plating. Due to the low melting point of silver foil, the melting point of ordinary mica sheets is about 600℃, and the melting point of synthetic mica sheets does not exceed 1100℃, which makes it difficult for them to maintain the original design pattern and form during the high-temperature firing process of building ceramics, and they are prone to high-temperature deformation. Therefore, silver foil is rarely used in building ceramics, or there are problems with weak metallic luster, short-lasting luster, and color development. In order to solve these problems and enable the surface decoration of tiles to present a better silver foil luster effect, we have developed a silver foil dry granular glaze with a silver foil luster effect and successfully applied it to building tiles. Summary of the invention
[0003] In view of the problems existing in the application of silver foil on architectural ceramics in the prior art, the present invention provides a silver foil dry granular glaze, a ceramic tile with a silver foil decorative effect and a preparation method thereof, so that the surface decoration of the ceramic tile can present a better silver foil gloss effect.
[0004] To solve the above problems, the present invention is implemented through the following technical solutions:
[0005] The first invention object of the present invention is:
[0006] Provided is a silver foil dry particle glaze, which comprises a silver foil core and a silver foil base slurry, wherein the mass ratio of the silver foil core to the silver foil base slurry is 1-5:95-99;
[0007] The silver foil core is a mica flake particle with a particle size of 4 to 120 meshes and a flake or granular shape;
[0008] The silver foil base slurry comprises the following components in percentage by weight:
[0009] 38-48% quartz powder, 13-22% aluminum oxide, 26-30% calcined talc, 10%-15% potassium oxide, 2-8% cerium oxide, 2-5% copper oxide, the sum of the above components is 100%;
[0010] Add 0.15% to 0.3% sodium tripolyphosphate, 0.12% to 0.18% sodium carboxymethyl cellulose, and 0% to 2% glaze colorant.
[0011] The second object of the present invention is:
[0012] A method for preparing the aforementioned silver foil dry particle glaze is provided, which comprises the following preparation steps:
[0013] S1. Preparation of silver foil base slurry:
[0014] Weigh the corresponding raw materials and the added sodium tripolyphosphate, sodium carboxymethyl cellulose and glaze colorant in proportion, add an appropriate amount of water, and grind them into a slurry with a 325 mesh residue fineness of 0.1-0.3%, a water content of 23-27%, a specific gravity of 1.85-1.95 g / ml, and a flow rate of 50-100 seconds (using a 100 ml volt cup to measure the flow rate) to prepare the silver foil shoe base slurry for standby use;
[0015] S2. Preparation of Silver Foil Dry Granule Glaze:
[0016] Use a 20-25 mesh sieve plate, spread a layer of 0.1-0.5mm silver foil core on it with a dry granulator, spray an appropriate amount of water or glue to moisten it, then cover the surface with diluted silver foil base slurry and stir evenly;
[0017] Repeat 1-2 times or more as needed, dry, stir evenly, sieve, then biscuit at 900-1100°C, keep the temperature constant for 30 minutes, cool, crush, and sieve 10-40 mesh particles to prepare the silver foil dry granular glaze;
[0018] The said coating refers to: applying a layer of glaze slurry wrapping cloth;
[0019] The diluted silver foil shoe base slurry is prepared by adding an appropriate amount of water to the silver foil shoe base slurry, adjusting the specific gravity to 1.30-1.85 g / ml, and adjusting the glaze amount and the coating glaze amount to 150-400 g / m 2 The control and flow rate are prepared by controlling the outflow time of 100 ml volt cup to 30 to 38 seconds;
[0020] The glue described in step S2 includes the following components in parts by weight:
[0021] 100 parts of water, 5 parts of sodium carboxymethyl cellulose (CMC), 13 parts of ethylene glycol, 0.1 parts of sodium tripolyphosphate, and 0.12 parts of preservative.
[0022] The silver foil dry particle glaze (including silver foil core and silver foil base slurry) prepared by the above method has its firing temperature significantly increased, and the sintering temperature of the silver foil core mica flake particles reaches 1180-1220°C, while various performances remain good (traditional mica flakes burn out, deform, and lose brightness at 1150°C and cannot be used for high-temperature particles).
[0023] The silver foil core uses a special silver foil base slurry (a glaze slurry containing magnesium oxide, aluminum oxide and added with copper oxide, cerium oxide and other elements) to cover the mica flake particles, which solves the problem of mica flake particles being intolerant to high temperatures and enables it to be used in high-temperature fast-firing ceramics; through the debugging and optimization of the organic combination of silver foil dry granular glaze, matte dry granular glaze and base glaze, the problems of silver foil's short-lasting gloss, poor gloss and poor stability are solved.
[0024] The third invention object of the present invention is:
[0025] Provided is a method for preparing a ceramic tile with a silver foil decorative effect, comprising the following preparation steps:
[0026] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0027] S2. Printing a designed inkjet pattern onto the brick body A to obtain a brick body B;
[0028] S3. Using a distributing machine to the brick body B, apply the aforementioned silver foil dry granular glaze to obtain a brick body C;
[0029] S4. Apply glue to the brick body C using a jet printer to obtain a brick body D;
[0030] S5. Use a glaze pouring machine to pour matte dry granular glaze onto the brick body D to obtain a brick body E;
[0031] S6. The brick body E is fired at high temperature to obtain a brick body F;
[0032] S7. The brick body F is semi-polished and sorted to obtain the ceramic brick with silver foil decorative effect.
[0033] The preparation method of the ceramic tile with silver foil decorative effect is further optimized as follows:
[0034] The silver foil dry granular glaze: 38-70 g / m 2 Give alms.
[0035] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0036] The base glaze comprises the following raw material components in percentage by weight:
[0037] Potassium feldspar powder 33-45%, air knife kaolin 10-15%, calcite 8-12%, wollastonite powder 3-6%, quartz powder 4-8%, barium carbonate 9-13%, zinc oxide 4-6%, calcined talc 8-12%, aluminum oxide 3-8%, the sum of all components is 100%;
[0038] Add 0.12-0.18% sodium carboxymethyl cellulose and 0.15-0.3% sodium tripolyphosphate.
[0039] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0040] The mass percentage chemical composition of the base glaze is:
[0041] SiO2 48.5~54.8%, Al2O3 12.8~18%, Fe2O3 0~0.45%, CaO 9~13%, MgO 3~7%, Na2O 2.8~6%, K2O 0.3~2.0%, ZnO 1.5-6%, B2O3 0.3~1.6%, BaO 4~8%; the sum of all components is 100%.
[0042] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0043] The base glaze comprises the following preparation steps:
[0044] According to the base glaze formula, the corresponding raw material components and the additional sodium carboxymethyl cellulose and sodium tripolyphosphate are weighed, and an appropriate amount of water is added. The base glaze is prepared by ball milling, slurry discharge, two 325-mesh sieves, and high-intensity iron removal for three times.
[0045] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0046] The specific gravity of the glaze slurry of the bottom glaze is 1.87-1.97 g / ml, the flow rate is 35-65 seconds, and the glaze amount of the bottom glaze is 420-720 g / m 2 .
[0047] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0048] The matte dry granular glaze has the following raw material components in percentage by weight:
[0049] Potassium feldspar 40-58%, calcite 5-10%, calcite 6-16%, barium carbonate 5-10%, wollastonite 5-10%, zinc oxide 3-5%, aluminum oxide 3-8%, the sum of all components is 100%;
[0050] Add 0.12-0.18% sodium carboxymethyl cellulose and 0.15-0.3% sodium tripolyphosphate.
[0051] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0052] The mass percentage chemical composition of the matte dry granular glaze is:
[0053] SiO2 55~63%, Al2O3 17~21%, CaO 10~12%, MgO 0.9~5%, K2O 3.8~5.9%, Na2O 0.3~1.3%, Fe2O3 0.01~0.06%, TiO2 0~0.05%, BaO 3~6%, ZnO3~6%, loss on ignition 0~0.1%; the sum of all components is 100%.
[0054] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0055] The matte dry granular glaze comprises the following preparation steps:
[0056] According to the formula of matte dry granular glaze, the corresponding raw material components and the added sodium carboxymethyl cellulose and sodium tripolyphosphate are weighed, an appropriate amount of water is added, mixed evenly, melted at 1620°C, kept warm for 6 to 10 hours, and then slowly cooled to room temperature at a cooling rate of 6 to 20°C / h to precipitate crystals, and the crystals are crushed and screened into particles of 4 to 25 meshes to prepare the matte dry granular glaze.
[0057] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0058] The matte dry granular glaze: the specific gravity is controlled at 1.23-1.35g / ml, and the glaze amount is controlled at 380-500g / m 2 control.
[0059] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0060] The specific gravity of the glue is controlled at 1.15-1.25 g / ml and the dosage is controlled at 160-250 g / m 2 control.
[0061] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0062] The high-temperature firing time is 39 to 55 minutes, and the firing temperature is 1180° C. to 1210° C., that is, high-temperature fast firing.
[0063] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0064] The semi-polishing is to use an elastic grinding block to polish the brick surface, and the brightness after polishing is 25 to 35 degrees.
[0065] The fourth invention objective of the present invention is:
[0066] Provided is a ceramic tile with a silver foil decorative effect, which is prepared according to the above-mentioned method for preparing the ceramic tile with a silver foil decorative effect.
[0067] The ceramic tile with silver foil decorative effect prepared by the present invention is prepared by preparing silver foil dry granular glaze, matte dry granular glaze and bottom glaze, adjusting and optimizing the components and proportions thereof, enhancing the contrast between the silver foil dry granular glaze and the matte dry granular glaze by methods such as positioning application of the silver foil dry granular glaze and half-polishing of the dry granular glaze, obtaining a perfect silver foil effect by physical coloration of the silver foil core mica flake particles themselves, and solving the problems of weak metallic gloss, unlasting gloss and single color.
[0068] The silver foil dry granular glaze, ceramic tile with silver foil decorative effect and preparation method thereof of the present invention involve the following key technologies:
[0069] (I) Preparation of silver foil dry granular glaze:
[0070] The formula composition of silver foil dry granular glaze directly affects the metallic glitter effect of the product. In addition to having a silver foil glitter effect, the silver foil dry granular glaze also needs to be compatible with matte dry granular glaze, base glaze, etc.
[0071] In order to obtain the silver foil dry particle glaze that meets the production needs, this technical solution has been adjusted and optimized from the following aspects.
[0072] (1) Introduce high-purity mica flake particles as silver foil cores. Impure mica flakes are prone to blistering, which affects the quality of the silver foil core. The particle size of mica flake particles is 4 to 120 meshes, and the particle size is selected according to product requirements. According to the experimental comparison results of the present technical solution, the mica flake particles that are not within the selected particle size range have the problem that the glaze effect prepared is not smooth enough or the silver foil has weak flash. The mica flake particles within the selected range not only have a smooth glaze, but also have an obvious flash effect.
[0073] (2) The silver foil shoe base slurry formula was adjusted and optimized, and the matte dry granular glaze formula and the base glaze formula were adjusted and optimized accordingly. The ratio of magnesium oxide (introduced by burned talc) and aluminum oxide in the silver foil shoe base slurry formula was optimized, and the melting temperature, transparency, bonding degree and other performances were good. For details, see the optimization comparison results in Table 1.
[0074] (3) Introduce appropriate amounts of copper oxide and cerium oxide to increase the flash effect of silver foil:
[0075] The physical coloring produced by the mixed structural arrangement is mainly through the crystal precipitation of Cu and Ce during high-temperature firing. It appears silvery white with a slight light green tint on the macro scale. The semi-transparent coloring combined with the mica sheet itself has a significant silver foil effect. Therefore, appropriate amounts of copper oxide and cerium oxide are added to the formula; 2-8% cerium oxide and 2-5% copper oxide are added to the shoe base slurry formula, and the product effect is optimized according to the product effect.
[0076] 1)Introduction of copper oxide:
[0077] The introduction of CuO in the silver foil base slurry formula can promote the coloring of the silver foil core. Copper oxide exists in the glaze in the form of ions or colloidal particles, which enhances the absorption of light waves on the brick surface, strengthens the light reflection effect, presents a smooth and delicate texture, and makes the glaze smoother and improves the gloss of the glaze. In addition, the addition of copper oxide increases the density and hardness of the base slurry glaze, making the glaze more wear-resistant and scratch-resistant. Moreover, copper oxide has good high-temperature stability, is not easy to be reduced at high temperature, and is not easy to decompose and change, thereby maintaining the color of the brick surface pattern for a long time.
[0078] 2) Introduction of cerium oxide:
[0079] The introduction of SeO into the silver foil base paste formula can enhance the following effects:
[0080] A. Improve transparency: The introduction of cerium oxide significantly improves the high-temperature vitrification degree of the silver foil base glaze, making the silver foil core appear clear and transparent.
[0081] B. Improve glossiness: Cerium oxide can promote the growth of crystals in the glaze, forming a fine and uniform crystal structure, making the light appear more uniform and smooth when reflected on the surface, thereby improving the glossiness of the silver foil dry particles.
[0082] C. Improve stability: Cerium oxide can prevent other components in the shoe base glaze from undergoing redox reactions, maintain the chemical stability of the shoe base glaze layer, and effectively prevent the silver foil core from changing during the production and use process.
[0083] D. Enhance the silver foil sparkle effect: The physical properties of cerium oxide enable it to produce reflection, refraction, and interference phenomena in the glaze, thus forming a sparkling effect.
[0084] E. Enhance hardness and wear resistance: Cerium oxide can increase the hardness and wear resistance of silver foil dry particle glaze, thereby improving the surface hardness and wear resistance of the product.
[0085] (4) Introduce appropriate amount of quartz powder:
[0086] Since a large amount of magnesium oxide and aluminum oxide are added to the silver foil base slurry formula, in order to solve the problem of high-temperature fusion adaptation of silver foil dry granular glaze and matte dry granular glaze, this project effectively solves the problem of combining the two dry granular glazes, as well as the problem of combining with the base glaze, by introducing an appropriate amount of quartz powder into the silver foil base slurry formula. The three are tightly combined by high-temperature firing, thereby ensuring the durability of the silver foil effect.
[0087] (5) Introducing alumina powder:
[0088] The silver foil dry granule glaze introduces alumina (Al2O3), which plays a significant role in the glaze. It has a high melting point and stable chemical properties. By introducing alumina, the melting temperature of the silver foil core can be significantly increased. In addition, the higher melting temperature can prevent the glaze layer on the surface of the silver foil core from having enough time to discharge gas before high-temperature fusion and sealing. It avoids defects such as bubbling and pinholes, thereby ensuring the good performance of the silver foil dry granule glaze; alumina has a certain high-temperature viscosity to ensure the molding and organic combination of the dry particles.
[0089] (II) Optimization of biscuit firing process:
[0090] Different from the melting and quenching process of ordinary fired frit dry particles, since the silver foil core mica flakes are pure dry flakes, and the silver foil base slurry is raw glaze, the two are combined through the composite and will naturally crack after drying. Therefore, the biscuit firing process is adopted. After many experiments and summaries, the well-mixed raw materials are placed in a furnace, biscuit fired at 900-1100℃, kept at a constant temperature for 30 minutes, cooled, crushed, and screened 4-120 mesh dry particles to obtain silver foil dry particle glaze. The silver foil core and the silver foil base slurry are integrated, thereby improving the bonding property.
[0091] (III) Optimization of particle size of silver foil dry granular glaze:
[0092] The particle size of the silver foil dry granular glaze has a great influence on the glitter effect of the glaze surface. The finer the particles, the worse the glitter effect. When the particles of the silver foil dry granular glaze are coarse, the glaze surface will also be rough during the subsequent glazing, and the product quality is low.
[0093] The invention crushes the fired silver foil dry granular glaze and screens the particles, and screens 4-6 meshes, 10-40 meshes and 60-100 meshes respectively.
[0094] Table 1 Effect of silver foil dry granular glaze fineness on glaze effect
[0095]
[0096] Through experimental comparison, it is found that when the particle size of the silver foil dry granular glaze is controlled at 10-40 mesh, the glaze effect is optimal. Therefore, in the preparation process, the silver foil dry granular glaze of 10-40 mesh is preferably selected for use. BRIEF DESCRIPTION OF THE DRAWINGS
[0097] Figure 1 This is a real-life rendering of the ceramic tile with silver foil decorative effect of the present invention (1220°C).
[0098] Figure 2 This is a real-life rendering of the ceramic tile with silver foil decorative effect of the present invention (1185°C).
[0099] Figure 3 The present invention is a flow chart of the preparation process of the ceramic tile with silver foil decorative effect. DETAILED DESCRIPTION
[0100] In order to make the application, technical scheme and advantages of the present invention more clear, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the embodiments are only used to illustrate the present invention, but not to limit the protection scope of the present invention. All simple improvements to the preparation method of the present invention under the premise of the concept of the present invention belong to the protection scope of the present invention.
[0101] Example 1
[0102] A method for preparing a ceramic tile with a silver foil decorative effect, comprising the following preparation steps:
[0103] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0104] S2. Printing a designed inkjet pattern onto the brick body A to obtain a brick body B;
[0105] S3. Using a distributing machine to the brick body B, apply the aforementioned silver foil dry granular glaze to obtain a brick body C;
[0106] S4. Apply glue to the brick body C using a jet printer to obtain a brick body D;
[0107] S5. Use a glaze pouring machine to pour matte dry granular glaze onto the brick body D to obtain a brick body E;
[0108] S6. The brick body E is fired at high temperature to obtain a brick body F;
[0109] S7. The brick body F is semi-polished and sorted to obtain the ceramic brick with silver foil decorative effect.
[0110] The silver foil dry granular glaze comprises a silver foil core and a silver foil base slurry, and the mass ratio of the silver foil core to the silver foil base slurry is 3:97;
[0111] The silver foil core is a mica flake particle with a particle size of 10 to 40 meshes and a flake or granular shape;
[0112] The silver foil base slurry comprises the following components in percentage by weight:
[0113] Quartz powder 38%, aluminum oxide 16%, calcined talc 28%, potassium oxide 12%, cerium oxide 4%, copper oxide 2%, the total amount is 100%;
[0114] Add 0.15% sodium tripolyphosphate, 0.12% sodium carboxymethyl cellulose and 1% glaze colorant.
[0115] Add appropriate amount of water to mix, the amount of water added is: total dry material (excluding added raw materials): water = 1:0.26 mass ratio;
[0116] The silver foil dry granular glaze: 55 g / m 2 Give alms.
[0117] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0118] The base glaze comprises the following raw material components in percentage by weight:
[0119] Potassium feldspar powder 38%, air knife kaolin 15%, calcite 11%, wollastonite powder 4%, quartz powder 4%, barium carbonate 9%, zinc oxide 4%, calcined talc 9%, aluminum oxide 6%;
[0120] Added: sodium carboxymethyl cellulose 0.15%, sodium tripolyphosphate 0.2%;
[0121] Add appropriate amount of water to mix, the amount of water added is: total dry material (excluding added raw materials): water = 1:0.28 mass ratio;
[0122] The base glaze comprises the following preparation steps:
[0123] The base glaze is prepared by weighing the corresponding raw material components according to the base glaze formula, ball milling, slurry discharge, passing through two 325-mesh sieves, and high-intensity iron removal for three times.
[0124] The specific gravity of the base glaze slurry is 1.89 g / ml, the flow rate is 55 seconds, and the glazing amount of the base glaze is 520 g / m2.
[0125] The matte dry granular glaze has the following raw material components in percentage by weight:
[0126] Potassium feldspar 53%, calcite 9%, calcite 15%, barium carbonate 6%, wollastonite 8%, zinc oxide 4%, aluminum oxide 5%;
[0127] Add 0.15% sodium carboxymethyl cellulose and 0.15% sodium tripolyphosphate;
[0128] Add appropriate amount of water to mix, the amount of water added is: total dry material (excluding added raw materials): water = 1:0.28 mass ratio;
[0129] The matte dry granular glaze comprises the following preparation steps:
[0130] According to the formula of matte dry granular glaze, the corresponding raw material components are weighed, mixed evenly, melted at 1620°C, kept warm for 8 hours, and then slowly cooled to room temperature at a cooling rate of 10°C / h to precipitate crystals, crushed, and screened to obtain 20-mesh dry granules to prepare the matte dry granular glaze.
[0131] The matte dry granular glaze: the specific gravity is controlled at 1.30g / ml, and the glaze amount is controlled at 420g / m 2 control.
[0132] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0133] The specific gravity of the glue is controlled at 1.20 g / ml and the dosage is controlled at 180 g / m 2 control.
[0134] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0135] The high-temperature firing time is 42 minutes, and the firing temperature is 1195° C., that is, high-temperature and fast firing.
[0136] The preparation method of the ceramic tile with silver foil decoration effect of the present invention is further optimized as follows:
[0137] The semi-polishing is to polish the brick surface using an elastic grinding block, and the brightness after polishing is 30 degrees.
[0138] The ceramic tile with silver foil decorative effect prepared according to the above embodiment not only has a smooth glaze surface, but also has an obvious flashing effect. Figure 1 .
[0139] Product performance test:
[0140] The indicators of the tested products are shown in Table 2.
[0141] Table 2 Routine inspection results of product quality (size 600×900×9.8mm)
[0142]
[0143]
[0144] Table 3 Special inspection results of product quality
[0145]
[0146] Table 4 Product quality special 2 test results
[0147]
[0148] The product has passed routine inspections and special inspections and tests. The silver foil dry granular glaze of the present invention introduces mica flake particles, and uses silver foil base slurry to coat the mica flake particles in an appropriate amount. The obtained silver foil dry granular glaze has greatly increased the firing temperature of the mica flake particles, and it maintains its original shape after being subjected to a high temperature of 1185°C to 1220°C. By optimizing the process formula, the silver foil dry granular glaze not only satisfies the silver foil flash effect, but also solves the problem of high-temperature adaptation of the silver foil dry granular glaze with matte dry granular glaze, base glaze, etc. The product has good performance after testing.
[0149] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0150] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0151] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0152] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0153] Unless otherwise stated, percentages and parts are by mass.
[0154] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0155] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
Claims
1. A silver foil dry granular glaze, characterized in that: It includes a silver foil core and a silver foil base slurry, wherein the mass ratio of the silver foil core to the silver foil base slurry is 1-5:95-99; The silver foil core is a mica flake particle with a particle size of 4 to 120 meshes and a flake or granular shape; The silver foil base slurry comprises the following components in percentage by weight: 38-48% quartz powder, 13-22% aluminum oxide, 26-30% calcined talc, 10%-15% potassium oxide, 2-8% cerium oxide, 2-5% copper oxide, the sum of the above components is 100%; Add 0.15% to 0.3% sodium tripolyphosphate, 0.12% to 0.18% sodium carboxymethyl cellulose, and 0% to 2% glaze colorant.
2. A method for preparing the silver foil dry granular glaze according to claim 1, characterized in that: It comprises the following preparation steps: S1. Preparation of silver foil base slurry: Weigh the corresponding raw materials and the added sodium tripolyphosphate, sodium carboxymethyl cellulose and glaze colorant in proportion, add an appropriate amount of water, and grind them into a slurry with a 325 mesh residue fineness of 0.1-0.3%, a water content of 23-27%, a specific gravity of 1.85-1.95 g / ml, and a flow rate of 50-100 seconds to prepare the silver foil shoe base slurry for standby use; S2. Preparation of Silver Foil Dry Granule Glaze: Use a 20-25 mesh sieve plate, spread a layer of 0.1-0.5mm silver foil core on it with a dry granulator, spray an appropriate amount of water or glue to moisten it, then cover the surface with diluted silver foil base slurry and stir evenly; Repeat 1-2 times or more as needed, dry, stir evenly, sieve, then biscuit at 900-1100°C, keep the temperature constant for 30 minutes, cool, crush, and sieve 10-40 mesh particles to prepare the silver foil dry granular glaze; The diluted silver foil shoe base slurry is prepared by adding an appropriate amount of water to the silver foil shoe base slurry, adjusting the specific gravity to 1.30-1.85 g / ml and the glazing amount to 150-400 g / m 2 The control and flow rate are controlled to be 30 to 38 seconds; The glue described in step S2 includes the following components in parts by weight: 100 parts of water, 5 parts of sodium carboxymethyl cellulose, 13 parts of ethylene glycol, 0.1 parts of sodium tripolyphosphate, and 0.12 parts of preservative.
3. A method for preparing a ceramic tile with a silver foil decorative effect, characterized in that: It comprises the following preparation steps: S1. preparing a body and applying a base glaze to the body to obtain a brick body A; S2. Printing a designed inkjet pattern onto the brick body A to obtain a brick body B; S3. Using a distributing machine, apply the silver foil dry granular glaze according to claim 1 to the brick body B to obtain a brick body C; S4. Apply glue to the brick body C using a jet printer to obtain a brick body D; S5. Use a glaze pouring machine to pour matte dry granular glaze onto the brick body D to obtain a brick body E; S6. The brick body E is fired at high temperature to obtain a brick body F; S7. The brick body F is semi-polished and sorted to obtain the ceramic brick with silver foil decorative effect.
4. The method for preparing a ceramic tile with silver foil decorative effect according to claim 3, characterized in that: The base glaze comprises the following raw material components in percentage by weight: Potassium feldspar powder 33-45%, air knife kaolin 10-15%, calcite 8-12%, wollastonite powder 3-6%, quartz powder 4-8%, barium carbonate 9-13%, zinc oxide 4-6%, calcined talc 8-12%, aluminum oxide 3-8%, the sum of all components is 100%; Add 0.12-0.18% sodium carboxymethyl cellulose and 0.15-0.3% sodium tripolyphosphate.
5. The method for preparing a ceramic tile with silver foil decorative effect according to claim 4, characterized in that: The mass percentage chemical composition of the base glaze is: SiO2 48.5~54.8%, Al2O3 12.8~18%, Fe2O3 0~0.45%, CaO 9~13%, MgO 3~7%, Na2O 2.8~6%, K2O 0.3~2.0%, ZnO 1.5-6%, B2O3 0.3~1.6%, BaO 4~8%; the sum of all components is 100%.
6. The method for preparing a ceramic tile with silver foil decorative effect according to claim 4, characterized in that: The base glaze comprises the following preparation steps: According to the base glaze formula, the corresponding raw material components and the additional sodium carboxymethyl cellulose and sodium tripolyphosphate are weighed, and an appropriate amount of water is added. The base glaze is prepared by ball milling, slurry discharge, two 325-mesh sieves, and high-intensity iron removal for three times.
7. The method for preparing a ceramic tile with silver foil decorative effect according to claim 3, characterized in that: The matte dry granular glaze has the following raw material components in percentage by weight: Potassium feldspar 40-58%, calcite 5-10%, calcite 6-16%, barium carbonate 5-10%, wollastonite 5-10%, zinc oxide 3-5%, aluminum oxide 3-8%, the sum of all components is 100%; Add 0.12-0.18% sodium carboxymethyl cellulose and 0.15-0.18% sodium tripolyphosphate.
8. The method for preparing a ceramic tile with silver foil decorative effect according to claim 7, characterized in that: The mass percentage chemical composition of the matte dry granular glaze is: SiO2 55~63%, Al2O3 17~21%, CaO 10~12%, MgO 0.9~5%, K2O 3.8~5.9%, Na2O0.3~1.3%, Fe2O3 0.01~0.06%, TiO2 0~0.05%, BaO 3~6%, ZnO3~6%, loss on ignition 0~0.1%; the sum of all components is 100%.
9. The method for preparing a ceramic tile with silver foil decorative effect according to claim 7, characterized in that: The matte dry granular glaze comprises the following preparation steps: According to the formula of matte dry granular glaze, the corresponding raw material components and the added sodium carboxymethyl cellulose and sodium tripolyphosphate are weighed, an appropriate amount of water is added, mixed evenly, melted at 1620°C, kept warm for 6 to 10 hours, and then slowly cooled to room temperature at a cooling rate of 6 to 20°C / h to precipitate crystals, and the crystals are crushed and screened into particles of 4 to 25 meshes to prepare the matte dry granular glaze.
10. A ceramic tile with silver foil decorative effect, characterized in that: The ceramic tile is prepared according to the method for preparing the ceramic tile with silver foil decorative effect according to claim 3.
Citation Information
Patent Citations
Mica sheet decorative ceramic glazed tile and preparation method thereof
CN110451802A
Low-gloss ceramic tile with stone-like effect and preparation method thereof
CN111116238A
Black ceramic tile with three-dimensional glittering effect and preparation method thereof
CN114249586A
Preparation method of one-time gold-plated dry granular glaze rock plate
CN114804928A
Ceramic product with metallic luster and preparation method thereof
CN117447238A
Cited By
Preparation method and application of foil crystal diamond or microcrystal diamond
CN119977335A